Good Corporate Governance dan Corporate Social Responsibility terhadap Kinerja Perusahaan dengan Gender Diversity sebagai Variabel Moderasi - Annisa, Diana; Sumiati, Ati; Purwohedi, Unggul (LPPM Universitas Negeri Jakarta, 2023)
This study aims to determine the effect of good corporate governance and corporate social responsibility on company performance with gender diversity as a moderating variable in the Basic and Chemical Industry Sectors listed on the Indonesia Stock Exchange for the 2020-2021 period. This study uses quantitative methods with secondary data sourced from the company's annual report and sustainability report. The research sample of 54 companies was selected using simple random sampling technique. The data analysis techniques used include multiple linear regression analysis and moderation, as well as hypothesis testing. The results showed that the independent board of commissioners (X1) had a significant positive effect on company performance, the audit committee (X2) had a significant negative effect on company performance. Meanwhile, managerial ownership (X3) and corporate social responsibility (X4) have no effect on company performance. In addition, gender diversity (z) is able to moderate the effect of independent commissioners and audit committees on company performance and gender diversity (Z) is not able to moderate the effect of managerial ownership and corporate social responsibility on company performance.